Sistem Pakar Diagnosa Distrofi Otot Berbasis Web Menerapkan Metode Tsukamoto - Zalukhu, Ishak (ADA Research Center, 2024)
Muscular dystrophy is a group of diseases that cause muscles to become weak, lose mass, and lose function. A common problem that occurs in the general public is the difficulty of knowing the diagnosis of muscular dystrophy in the body based on the symptoms experienced due to the limited number of specialist doctor consultation services in the neighborhood where they live. Overcoming the problem of difficulty in knowing the diagnosis of muscular dystrophy that has been described above, in this study the authors built a web-based expert system for diagnosis of muscular dystrophy using the Tsukamoto method. If a patient with a severity status of exactly 5 is given a diagnosis of moderate severity muscular dystrophy. The results of this study indicate that the application of the Tsukamoto method in the process of diagnosing Muscular Dystrophy gives effective results to solve the problem of diagnosing Muscular Dystrophy in accordance with expert knowledge.